Assessment of Hormonal Indicators in Women of Reproductive Age with Polycystic Ovary Syndrome - Ibragimova Dilhumor (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting women of reproductive age and is associated with hormonal imbalance and metabolic disturbances. This study aimed to assess hormonal indicators in women diagnosed with PCOS and to identify key endocrine changes related to the condition. Serum levels of luteinizing hormone, follicle-stimulating hormone, testosterone, prolactin, and insulin were evaluated. The results showed increased levels of luteinizing hormone, testosterone, and insulin, along with an elevated LH/FSH ratio, indicating hyperandrogenism and insulin resistance. These findings highlight the importance of hormonal profiling in the diagnosis and management of PCOS. Early detection of hormonal alterations can contribute to improved reproductive outcomes and prevention of complications.